A short review of polymer-based electrospun nanofiber membranes for wastewater treatment - Nik Zuliani, Nik Kadir; Rosmawati, Naim (2M World Sdn Bhd, 2023)
This paper aims to review the various materials that can be used to develop a nanofiber membrane for wastewater treatment using the needleless electrospinning method. The needleless electrospinning technique is a promising method for producing nanofiber membranes as it allows for the creation of fibers with diameters in the nanometer range, leading to high surface area to volume ratio and increased membrane efficiency. The materials that will be reviewed in this paper include polymers such as polyvinyl alcohol, polyethylene oxide, and polyacrylonitrile. These polymers have been widely studied for their potential use in wastewater treatment due to their high mechanical strength and chemical stability. The paper will also review the use of natural materials such as chitosan, which have been shown to have good biocompatibility and biodegradability properties. Finally, the paper will discuss the potential applications of the nanofiber membrane in wastewater treatment, including the removal of pollutants such as heavy metals, dyes, and bacteria. Overall, this paper aims to provide a comprehensive overview of the materials that can be used to develop a nanofiber membrane for wastewater treatment using the needleless electrospinning method and the potential applications for the wastewater treatment.